The Effect of Intellectual Intelligence (IQ), Emotional Intelligence (EQ) and Spiritual Intelligence (SQ) on Character - Muhammad Kris Yuan Hidayatulloh; Ulliya Mufrodatul; Dian Kusuma Wardani (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to determine the influence of intellectual intelligence (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ) simultaneously and partially to the character of MA students Darun Najah Karangploso Malang. This type of research is quantitative, the population of this research is all students of MA Darun Najah class with the sample used in this research amount 40 people and the sampling technique used is random sampling. The data collection instrument used a questionnaire with a Likert scale, each of which has been tested and has met the validity and reliability requirements and data analysis using multiple linear regression. The results of multiple linear analysis show that the variables Intellectual Intelligence (IQ), Emotional Intelligence (EQ) and Spiritual Intelligence (SQ) simultaneously have a significant positive influence on the character of MA students Darun Najah. This can be proven by the results of the f test with a significant value (Sig) of 0.11 because the sig. smaller than 0.05. Based on the results of the t test (partial) all variables have no effect on the character of MA students. Darun Najah Karangploso Malang.